The Edinburgh companion to W.B. Yeats and the arts - Armstrong, Charles I. 1969-; Paterson, Adrian; Walker, Tom 1981- (Edinburgh University Press, 2024)
"W. B. Yeats was not only a poet but also a cultural revolutionary. A restless collaborator, he fostered countless artistic enterprises, from the Abbey Theatre to the Cuala Press, and pursued various inter-artistic media and forums for his work. From childhood co-creations with his siblings to the arresting combination of sound and movement in his final play, The Death of Cuchulain, his work also repeatedly addresses and incorporates music, dance, and the visual, material and theatrical arts with remarkable intensity. For him, literature was a vital thing that engaged, in one form or another, all the senses. This volume's newly commissioned chapters analyse afresh such engagements. Bringing together scholars of literature, aesthetics, cultural history and specialists in drama, music, dance and the visual arts, they provide a broad range of historical, conceptual, and disciplinary approaches and perspectives."
Keywords: Yeats, William Butler -- 1865-1939; Künste; Yeats, W. B / (William Butler) / 1865-1939 / History and criticism; Performing arts and literature; Aufsatzsammlung